LITERASI TERKINI DALAM PEMBELAJARAN BIPA PADA ERA REVOLUSI DIGITAL - Anggaira, Aria Septi (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The Vision of Indonesian Language for Foreign Speakers (BIPA) is the implementation of teaching that is able to enhance Indonesia's positive image in the international world in order to make Indonesian as a broad language of communication at the level of nations. To be able to realize the integrated learning objectives of BIPA culture, BIPA teachers must always update information, especially human, art, culture; more broadly is Indonesian culture. In this case, the instructors in the BIPA program are required to be able to develop systematic learning tools. BIPA teachers must be able to become the front guard in civilizing Indonesia through new literacy, including data literacy, technology literacy, and human literacy. This condition marks the beginning of the era of the digital industry world which has become a paradigm and reference in the present order of life.